Organic ultraviolet filters regulate hyaluronan metabolism in human epidermal keratinocytes through the phosphatidylinositol 3-kinase pathway - Chang, Kai-Yen; Yang, Chao-Hsun; Chou, Hsin-Yi; Chen, Kuan-Chun; Huang, Yu-Chun (Toxicology in vitro, 2023)
Chronic exposure of skin to ultraviolet (UV) radiation is responsible for skin ageing, which includes degradation of the epidermal and dermal layers. Filtering UV light is key in the sunscreen industry. We studied the effects of organic UV filters on hyaluronan (HA) metabolism and skin hydration in human HaCaT keratinocytes. The gene expression of HA receptors, HA synthase (HAS), hyaluronidase (HYAL), and water channel aquaporin 3 (AQP3) was evaluated by quantitative RT–PCR. The state of oxidative stress was determined by measuring the intracellular levels of reactive oxygen species (ROS). The results showed that five organic UV filters reduced the extracellular contents of HA, and a phosphatidylinositol 3-kinase (PI3K) inhibitor partially restored the decreased HA levels after octinoxate, octocrylene, and oxybenzone treatment. The expression levels of HA receptors, including cluster of differentiation 44 (CD44), receptor for hyaluronic acid-mediated motility (RHAMM), and toll-like receptors (TLRs), were determined. Avobenzone, octinoxate, oxybenzone, and padimate O exerted inhibitory effects on RHAMM expression. Oxybenzone led to a significant increase in CD44 and AQP3 expression. Both octinoxate and octocrylene increased TLR4 expression but decreased ROS accumulation by activating the PI3K pathway. However, the organic UV filters differentially regulated the mRNA expression of HAS and HYAL. Taken together, these results suggest that certain organic UV filters regulate HA metabolism in human keratinocytes in a PI3K pathway-dependent manner. •Avobenzone enhanced aquaporin 3 expression and have the potential to maintain skin hydration.•Octinaxate promoted toll-like receptor 4 expression and decreased intracellular oxidative stress.•Octocrylene repressed aquaporin 3 expression and intracellular oxidative stress.•Oxybenzone increased hyaluronidases, aquaporin 3, and CD44 expression.•Octinoxate, octocrylene, and oxybenzone decreased hyaluronan production through the phosphatidylinositol 3-kinase pathway.